PENGARUH TETRAKSIKLIN TERHADAP KERENTANAN OLEH SERANGAN PENYAKIT MAS, PERTUMBUHAN DAN DAYA TETAS TELUR LELE DUMBO (Clarias gariepinus) - Kamiso H. N.; Triyanto Triyanto (Universitas Gadjah Mada, 1996)
Study was conducted to find out the effect of tetracycline medication to suspectibility against MAS, growth rate and hatching rate of African catfish (Clarias gariepinus). The result indicated that intraperitoneal injection of tetracycline (50 mg/kg fish) could decrease the growth rate of fish significantly (P<0.05). However, this medication did not have significant effect to suspectibility of fish against A. hydrophila the causative agent of MAS. Intraperitoneal injection of tetracycline (50 mg/kg fish) in african catfish brooders two weeks before spawning also did not effect fertility or hatching rate of eggs.